2023
DOI: 10.1021/acs.jmedchem.2c01767
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Optimization of CBL0137 for Human African Trypanosomiasis Lead Drug Discovery

Abstract: The carbazole CBL0137 (1) is a lead for drug development against human African trypanosomiasis (HAT), a disease caused by Trypanosoma brucei. To advance 1 as a candidate drug, we synthesized new analogs that were evaluated for the physicochemical properties, antitrypanosome potency, selectivity against human cells, metabolism in microsomes or hepatocytes, and efflux ratios. Structure–activity/property analyses of analogs revealed eight new compounds with higher or equivalent selectivity indices (5j, 5t, 5v, 5w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Two compounds from this series have previously been advanced into PK studies and 8c was found to have excellent exposure in the brain and, at 40 mg/kg per os (P.O. ; oral administration), it had a brain:blood ratio at 1 h of 5.1 (male) and 4.1 (female); and at 4 h it was 3.6 (male) and 5.2 (female; Singh et al, 2023 ). Further SAR scoping with a focus on reducing the lipophilicity and maintaining the potency is underway.…”
Section: Resultsmentioning
confidence: 99%
“…Two compounds from this series have previously been advanced into PK studies and 8c was found to have excellent exposure in the brain and, at 40 mg/kg per os (P.O. ; oral administration), it had a brain:blood ratio at 1 h of 5.1 (male) and 4.1 (female); and at 4 h it was 3.6 (male) and 5.2 (female; Singh et al, 2023 ). Further SAR scoping with a focus on reducing the lipophilicity and maintaining the potency is underway.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, recent studies have reported encouraging results for the use of CBL137 as a potential latency-reversing agent in HIV-1 infection, and even as a lead for drug discovery efforts against human African trypanosomiasis, further underscoring the potential of CBL137 as a therapeutic against various infectious diseases. 76,77…”
Section: Discussionmentioning
confidence: 99%